(untitled) (Texas Journal of Medical Science, 2024)
Smoking has been shown to have a detrimental impact on various aspects of adolescent health, including physical, mental, and social health. Smoking increases the risk of developing health problems. Smoking rates among adolescents are very high, leading to various adverse health effects and social consequences.This study will use a cross-sectional research design, which is a type of observational research design. The design in this study is a non-equivalent control group design with pre-test and post-test. Due to the grouping of sample members in the experimental group and control group. This study divided the group into two, namely the first group was given android-based quit-smoking education, and the second group was not given the intervention. The research strategy used mixed research methods, with quantitative research as the main research design and qualitative research. The study showed that adolescents who participated in this education program had better knowledge about the dangers of smoking, as well as more positive attitudes towards smoking cessation. In addition, adolescents also showed changes in their smoking-related behaviors after participating in the education, so Android-based quit-smoking education can provide long-term benefits in reducing smoking prevalence among adolescents and promoting healthy lifestyles and awareness of the importance of lung health and prevention of smoking-related diseases. Along with the development of technology and the expansion of smartphone use among adolescents, the implementation of Android-based quit-smoking education not only provides benefits in adolescent health education but also has broader social implications